ANALISIS PENGARUH PENERAPAN ATRIBUTE CORPORATE GOVERNANCE TERHADAP TINGKAT KESEJAHTERAAN PEMEGANG SAHAM BANK-BANK UMUM - AJI, BAYU (EDUKA : Jurnal Pendidikan, Hukum, Dan Bisnis, 2018)
ABSTRAK This research examines whether implementation of the corporate governance attribute have an impact against the shareholders wealth of commercial bank. We hypothesize that percentage of independent board, existence of the audit committee, ownership structure, number of the board of directors, the profitability of commercial banks, and the size of commercial banks, as a representative of the corporate governance, have an impact against the shareholders wealth of commercial bank.This research uses several corporate governance attributes developed by Indonesia Stock Exchange (IDX) and Capital Market Supervisory Agency, and the shareholders wealth of commercial bank developed by Brigham and Houston (2001).According to Generalized least squared approach on pooling data. Overall, using profitabilty and firm size as controlling variable, the result that shareholders wealth of commercial banks have a negatively associated with the most part of the corporate governance attributes, but it have a posstively associated with number of the board of directors. The research has several implications to offer, one of which is that it could be taken as a guideline for shareholders and management of commercial banks. Moreover, the research provides some information and identities the sources of ineficency, which could, in turn, be used to assist commercial bank?s managements to boost the shareholders wealth.  Kata Kunci: Corporate Governance, Kesejahteraan, Bank